Student activism and the 13th Malaysian General Election: the second civil society wave after 1969 - Fadzil, Mohd Fauzi; Ku Samsu, Ku Hasnita (Universiti Putra Malaysia Press, 2015)
The 13th Malaysian General Election held on 5 May, 2013 witnessed the revival of the student movement in Malaysia. Civil society activism had been on the wane for more than 40 years as the student movement had been shackled by the Universities and College Universities Act or AUKU (Akta Universiti dan Kolej Universiti), which brought student movement activism under the control and subject of AUKU. The student movement managed to gain some latitude from AUKU in 2012 when it was amended, paving the way for students to participate more actively in the 2013 General Election. The true motive of the student movement was in fact not the gaining of political power, but to regain the universities' autonomy that had been lost in the 1970s. For this purpose the student movement, under their new organisation, Gerakan Mahasiswa 13 (GM13), launched several street demonstrations to exert pressure on the ruling government. This movement launched its manifesto in order to bring the attention of the ruling government to its demands. In the 13th General Election, the student movement played two major roles: firstly acting as a pressure group and secondly, disseminating information.